2 CM’DEN BÜYÜK ÜRİK ASİT TAŞLARINDA ORAL KEMOLİZ - TUNÇ, Burçin; ATAUS, Süleyman; ÖNAL, Bülent; ALAN, Cabir; YALÇIN, Veli; ÖNER, Armağan (Cerrahpaşa Medical Journal, 2019)
Background and Design.- By medical chemolysis, uric acid calculus can be dissolved and their recurrences can be avoided. Between 2000 and 2004, 12 patients applied to our clinics with uric acid calculus larger than 2 cm. We treated these patients with adequate hydration and potassium citrate (1 mEq/kg/day). For those who can not tolerate potassium citrate, sodium bicarbonate (650 mgr 3-4 times a day) was started. Each patient was given a pH paper to record urinary pH, and drug dozes were titrated until urinary pH 7.0 was reached. Allopurinol (300mgr/day) was given to the ones with hyperurisemia. Patients were followed-up with urinary sediment, urinary culture, and ultrasonography and/or computerized tomography. Results.- Mean age of the patients were found to be 51 (34-70). Eight patients had left, 4 had right kidney stone. One patient had solitary kidney. Mean stone size were 29 mm (20-40). All of the stones were dissolved in 3.7 (2- 6) months. None of the patients had urinary infection through out of the treatment. Conclusion.- Even for the uric acid stones larger than 2 cm, oral chemolysis can be the treatment of choice. It is simple, safe and inexpensive. However, it requires rigid compliance by the patient and strict follow-up.